Analisis Tatakelola Sasaran Keselamatan Pasien Pada Alur Pelayanan Penyakit Sepsis Di Rumah Sakit Tebet 2015 - Rasam, Rianayanti Asmira (UI Scholars Hub, 2017)
In the context of modern medicine, complexity hospital’s management is regarded as the primary cause of medical error (ME). The new healthcare paradigm of “Patient-Focused Care”, patient’s right to receive safe healthcare treatment is considered as main indicator in Standar Akreditasi Rumah Sakit of 2012 (SARS 2012) in Indonesia, through the implementation of 6 Patient Safety (KP) standards. In the category of emergency medical treatment, Sepsis is considered as a disease with high mortality and morbidity rate. The use of The International Classification of Diseases, based on Ninth Revision (ICD-9), have caused terminological confusion and contribute to the increase of sepsis mortality rate. Globally, sepsis’ mortality rate reaches 8 million/year or 24.000/day, with growth rate of 8-13% per-year. To ensure the effectiveness of KP standard implementation in sepsis medical treatment, a research on the implementation of 6 Targets of KP in RS Tebet is conducted. Using case study, qualitative and descriptive analysis, this research is performed in the course of April-May 2015. The research shows that effectiveness 6 Targets of KP implementation reaches 96,283%, with 5% margin of error. This research proves that implementation of 6 Targets of KP in healthcare treatment procedure for sepsis cases can reduce the risk of ME.